3
$\begingroup$

In solving an eigenvalue problem, I've come to following equation ($\lambda=1$): $$\begin{pmatrix} \cos(\theta) & \sin(\theta) \\ \sin(\theta) & -\cos(\theta) \end{pmatrix}\begin{pmatrix} a \\ b \end{pmatrix}=\begin{pmatrix} a \\ b \end{pmatrix}$$ Now, the solution says, "This matrix equation can be reduced to a single equation": $$a \sin(\frac{1}{2}\theta)=b\cos(\frac{1}{2}\theta)$$ I've been rotating trigonometric formulas to get to this, but I simply can't find the way. Could you help me with this, or at least give me a hint?

$\endgroup$
5
$\begingroup$

$$\begin{pmatrix} \cos(\theta) & \sin(\theta) \\ \sin\theta & -\cos\theta \end{pmatrix}\begin{pmatrix} a \\ b \end{pmatrix}\\=\begin{pmatrix} a\cos\theta+b\sin\theta \\ a\sin\theta-b\cos\theta \end{pmatrix}=\begin{pmatrix} a \\ b \end{pmatrix}$$ Which gives us the following system of equations: $$a\cos\theta+b\sin\theta=a\tag{1}$$ $$a\sin\theta-b\cos\theta=b\tag{2}$$

So from $(1)$ you have:

$$b\sin\theta=a(1-\cos\theta)$$

$$2b\sin(\frac \theta{2})\cos(\frac \theta{2})=a(2\sin^2(\frac \theta{2}))$$ $$b\cos(\frac \theta{2})=a\sin(\frac \theta{2})$$

$\endgroup$
5
$\begingroup$

Since the matrix has the eigenvalue 1, it's enough to consider only the first row. Rearrange to get $(1-\cos(\theta))a = \sin(\theta)b$ which if you expand by the right formulae, give you $2(\sin(\theta/2)^2)a = 2\sin(\theta/2)\cos(\theta/2)b$. Now, if your matrix has to be non-identity, then this will give you the equation want.

$\endgroup$
2
$\begingroup$

The matrix system corresponds to the following system of equations \begin{equation} \cos(\theta)\,a + \sin(\theta) b = a \,, \\ \sin(\theta)\,a - \cos(\theta) b = b \, \end{equation} Multiplying the first equation by $\sin(\theta)$ and the second by -$\cos(\theta)$ gives \begin{equation} \sin(\theta)\,\cos(\theta)\,a + \sin(\theta)^2 b = a\,, \\ -\sin(\theta) \cos(\theta) \,a + \cos(\theta)^2 b = -b \, \end{equation}

Add the two equations, and the simplify the resulting equation, you get

$$ b( 1+\cos(\theta) ) = a\,\sin(\theta) $$

Using the identity $ \cos(\theta) = 2\cos(\theta /2)^2 -1 $ and $\sin(\theta) = 2 \sin(\theta /2) \cos(\theta /2) $ in the above equation yields

$$ 2 b \cos(\theta /2)^2 = 2 a \sin( \theta /2 ) \cos( \theta /2 )$$

Dividing both sides of the equation by $\cos(\theta /2)$ gives the result

$$ b \cos(\theta /2) = a \sin( \theta /2 ) $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.